The effect of xanthan gum as an elicitor on guard cell function and photosynthesis in Vicia faba - Ördög, Attila; Bernula, Dóra; Wodala, Barnabás (Acta Biologica Szegediensis, 2014)
Many plant species respond to pathogen attacks by closing stomata in a process called basal resistance. Pathogen-associated molecular patterns (PAMPs) are recognized by pattern recognition receptors (PRRs). This interaction can lead to the activation of different signaling cascades, which can lead to stomatal closure. The immune-active behavior of the bacterial elicitor xanthan gum has been demonstrated in barley where a xanthan treatment lead to the accumulation of the enzyme ß-1,3 glucanase. However, its short-term physiological effects have not been investigated yet. In this study we investigated the effect of xanthan gum on the guard cell function. Xanthan gum applied at dawn can induce stomatal closure, reduce stomatal conductance and the rate of CO2 assimilation, and it can also reduce PSII photochemistry in guard cells.